In-situ measurement and monitoring of melt pool temperature using two-wavelength pyrometry with photodiodes in laser powder bed fusion - Renwu Jiang (22685111) (2025)
Melt pool temperature is critical for assessing component quality in laser powder bed fusion (LPBF), yet its high-precision in-situ measurement remains challenging due to rapid thermal cycles and material emissivity variations. This study developed a high-temporal-resolution (up to 100 kHz) LPBF melt pool temperature in-situ measurement and monitoring system based on two-wavelength pyrometry with photodiodes centered at 800 nm and 880 nm. By employing an in-situ traceable blackbody calibration method, the system achieved a temperature measurement error of less than 1.5%. The system was validated through single-track printing of AlMgScZr under varying process parameters, revealing a clear correlation between single-track morphology, melt pool dimensions, and melt pool temperature. The results indicated that discontinuous tracks correspond to over 8% of temperature points below the melting point, whereas continuous tracks exhibited fewer than 8%. Frequency-domain analysis further established the dominant frequency as a reliable indicator of melt pool mode, with conduction mode corresponding to frequencies below 33 Hz and keyhole mode to those above 44 Hz. And the underlying transition mechanism was elucidated through melt pool dynamics. Overall, the proposed approach enables accurate, cost-effective, and high-speed temperature measurement under realistic LPBF conditions, demonstrating strong potential for real-time defect detection and quality control.